Proteomic Identification of Oxidized Proteins in Entamoeba histolytica by Resin-Assisted Capture: Insights into the Role of Arginase in Resistance to Oxidative Stress. - Preeti Shahi; Meirav Trebicz-Geffen; Shruti Nagaraja; Sharon Alterzon-Baumel; Rivka Hertz; Karen Methling; Michael Lalk; Serge Ankri (Public Library of Science (PLoS), 2016)
Entamoeba histolytica is an obligate protozoan parasite of humans, and amebiasis, an infectious disease which targets the intestine and/or liver, is the second most common cause of human death due to a protozoan after malaria. Although amebiasis is usually asymptomatic, E. histolytica has potent pathogenic potential. During host infection, the parasite is exposed to reactive oxygen species that are produced and released by cells of the innate immune system at the site of infection. The ability of the parasite to survive oxidative stress (OS) is essential for a successful invasion of the host. Although the effects of OS on the regulation of gene expression in E. histolytica and the characterization of some proteins whose function in the parasite's defense against OS have been previously studied, our knowledge of oxidized proteins in E. histolytica is lacking. In order to fill this knowledge gap, we performed a large-scale identification and quantification of the oxidized proteins in oxidatively stressed E. histolytica trophozoites using resin-assisted capture coupled to mass spectrometry. We detected 154 oxidized proteins (OXs) and the functions of some of these proteins were associated with antioxidant activity, maintaining the parasite's cytoskeleton, translation, catalysis, and transport. We also found that oxidation of the Gal/GalNAc impairs its function and contributes to the inhibition of E. histolytica adherence to host cells. We also provide evidence that arginase, an enzyme which converts L-arginine into L-ornithine and urea, is involved in the protection of the parasite against OS. Collectively, these results emphasize the importance of OS as a critical regulator of E. histolytica's functions and indicate a new role for arginase in E. histolytica's resistance to OS.